Having Fun with Computer Programming and Games: Teacher and Student Experiences - McInerney, Clare (Teaching Fundamental Concepts of Informatics, 2010)
There has been a decline in the number of students studying mathematics, science and computing at third-level in Ireland. This may be because Ireland does not have a computing curriculum. However, in the UK higher education computing students fell in spite of the existence of such curriculum. According to teachers, student engagement and having a fun and exciting experience are essential ingredients when teaching computing to second-level students through a computing curriculum or other interventions. The Lero Education and Outreach program has developed a set of materials “Having fun with Computer Programming and Games” for second-level students aged 15-16. The goal is to engage students in computing and to offer them an enjoyable and positive experience. Working with two second-level ICT teachers, we designed a set of materials during summer 2008 that have been deployed in a number of schools.